2003
DOI: 10.2337/diacare.26.3.917
|View full text |Cite
|
Sign up to set email alerts
|

Economic Costs of Diabetes in the U.S. in 2002

Abstract: AMERICAN DIABETES ASSOCIATIONOBJECTIVEdThis study updates previous estimates of the economic burden of diagnosed diabetes and quantifies the increased health resource use and lost productivity associated with diabetes in 2012.RESEARCH DESIGN AND METHODSdThe study uses a prevalence-based approach that combines the demographics of the U.S. population in 2012 with diabetes prevalence, epidemiological data, health care cost, and economic data into a Cost of Diabetes Model. Health resource use and associated medica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
111
0
2

Year Published

2006
2006
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 1,536 publications
(123 citation statements)
references
References 6 publications
3
111
0
2
Order By: Relevance
“…Diabetes mellitus presently affects an estimated 30 million people in the United States,3 with increases evident in every age group, in both sexes, in every racial/ethnic group, by all education levels, and in all income brackets 4. Despite significant advances in treatment and outcomes,5 the impact of diabetes mellitus continues to be substantial on cardiovascular complications, mortality,6 and resource use 7, 8, 9, 10. In response to the increasing prevalence and impact of diabetes mellitus, evidence‐based care guidelines11, 12, 13, 14 and performance measures have been developed for the care of patients with diabetes mellitus 15, 16, 17.…”
Section: Introductionmentioning
confidence: 99%
“…Diabetes mellitus presently affects an estimated 30 million people in the United States,3 with increases evident in every age group, in both sexes, in every racial/ethnic group, by all education levels, and in all income brackets 4. Despite significant advances in treatment and outcomes,5 the impact of diabetes mellitus continues to be substantial on cardiovascular complications, mortality,6 and resource use 7, 8, 9, 10. In response to the increasing prevalence and impact of diabetes mellitus, evidence‐based care guidelines11, 12, 13, 14 and performance measures have been developed for the care of patients with diabetes mellitus 15, 16, 17.…”
Section: Introductionmentioning
confidence: 99%
“…This is a great concern because physical inactivity is a relevant risk factor related to chronic diseases and early mortality (Admiraal et al 2011;Arsenault et al 2010;Beunza et al 2007;WHO 2006). Parallel to this there is increasing literature, identifying that chronic diseases have a significant burden over health care costs in both developed and developing countries (Arredondo et al 2005;Bahia et al 2012;Hogan et al 2003). Chronic diseases have been associated to higher expenditures and health care services, specially related to diabetes.…”
Section: Introductionmentioning
confidence: 99%
“…In Brazil, in a recent study (Bahia et al 2012) estimated the total yearly costs with all the diseases related to overweight and obesity around US$ 2.1 billion, which represents approximately 10 % of entire outpatient costs. In the United States of America, Hogan et al (2003) found that the direct and indirect costs related to medicines for diabetes control expenditures were US$ 132 billion.…”
Section: Introductionmentioning
confidence: 99%
“…The American Diabetes Association (ADA) estimated the national expenses of diabetes in the USA for 2002 to be US132 billion, increasing to US192 billion in 2020 [3]. Recently, biguanides, thiazolidinediones, sulfonylureas, D-phenylalanine and α-glucosidase inhibitors along with insulin are extensively used in the treatment of diabetes by a sustained reduction in hyperglycemia.…”
Section: Introductionmentioning
confidence: 99%